Strategi Pengembangan Desa Sayan Ubud, Kabupaten Gianyar, Bali, Sebagai Desa Wisata Berbasis Wisata Alam Bija - Thalia, Alinda; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
Sayan Village is one of the villages in Ubud that has a lot of potential to be used as a tourism village. The first three great potentials are natural tourism, potential opportunities for water tubing tourism, and also the potential of Puri Sayan as a heritage tourism object in Sayan Village, which is being planned by the village government and local communities. In addition to the three great potentials, Sayan Village also has the potential for water tourism with beji spring sources which are a source of water that is purified by the local community and is usually used for melukat. In this case, the researcher focused more on discussing the development of biology natural tourism which is currently used as the center of tourism village activities in Sayan Village. This study uses collection techniques in the form of observation, interviews, and documentation. The data analysis technique used is descriptive qualitative analysis and SWOT analysis. The technique of determining informants used purposive sampling technique. The results of this study contain the existing conditions of Desa Sayan based on tourism product components, namely attractions, amenities, accessibility, and ancilliary. And the strategy for developing SWOT-based Sayan Tourism Village. So that the strategies obtained produce the best ways to realize one of the missions of Desa Sayan as a sustainable tourism village. Keyword: Identification of Existing Conditions, SWOT Analysis, Natural Tourism, Sayan Tourism Village.